Contributive factors to the organizational trust of the middle managers of public elementary schools of the division of camarines norte - Marmol, Mnuel L. (San Miguel, Iriga City: University of Saint Anthony, 2000)
Contributive factors to the organizational trust of the middle managers of public elementary schools of the division of camarines norte.
Includes bibliographical references.
English
Keywords: middle managers